THE EFFECT OF CORPORATE GOVERNANCE AND EARNINGS INFORMATION ON BOND RATINGS AND YIELDS - MUNGNIYATI MUNGNIYATI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2009)
The purpose of this research is to analyze effect of corporate governance and earnings information on bond ratings and yields. The proxies of corporate governance are institutional ownership, independent commissioner, audit committee, and managerial ownership. While the proxy of earning information is unexpected earning. Logistic regression is used to examine first hypothesis, and multiple regression is used to examine second hypothesis. Samples are all bonds that issued before January 1st, 2005 and mature after December 31st, 2007 which are rated by PEFINDO. The companies that issued bonds besides banking and financial institution should be listed in Indonesia Stock Exchange. The result of this research indicates that corporate governance and earnings information influence bond ratings and yields. The existence of independent commissioner has significant influence on bond ratings and yields. The existence of audit committee has significant influence on bond yields.